Implementation of the Results of Fiscal Decentralization of Ukraine and the Countries of the European Union - TRUSOVA, Natalia V.; KOHUT, Inna A.; OSYPENKO, Svitlana A.; RADCHENKO, Nataliia G.; RUBTSOVA, Natalia N. (Journal of Advanced Research in Law and Economics, 2019)
The article presents the results of fiscal decentralization of Ukraine and the countries of the European Union as a process of restructuring and balancing the specific interests of all entities of redistributive relations, optimizing and improving the structure of the revenue segment of local budgets, and ensuring stable tax revenues through the improvement of the current taxation system. An analysis of the level of fiscal decentralization of the EU countries was carried out on the basis of indicators of fiscal autonomy and fiscal significance of local self-government. In order to increase the role of fiscal consolidation and filling local budgets in Ukraine, the timeliness of budget-tax reforms and their impact on the socio-economic development of the state have been substantiated. The empirical analysis was based on the fiscal rules of the decentralization of European countries that form the system-forming elements of the model of the tax on profits, providing a favorable fiscal space for business, motivating the effective use of budget funds by territorial communities. The target function of the optimization model, which determines the maximization of the fiscal decentralization index of local budgets, is proposed. Fiscal consolidation scenarios and their potential changes in Ukraine's GDP have been developed, subject to the introduction of the tax on withdrawn capital, as an alternative form of the tax on profits.